Appropriateness of a Telephone Health Line Referral System in a Pediatric Emergency Department - Correia de Oliveira, Susana (2022)
Introduction: Telephone health lines have been increasingly gaining popularity, offering healthcare counseling and triage to the population and resolving the need for unnecessary medical evaluations. This study aimed to characterize the health line referral pattern of the pediatric population to the emergency department of a level II hospital and assess its appropriateness. Methods: Cross-sectional investigation of all children referrals using the SNS 24 phone line from July 1st to December 31st, 2019. Good referrals were defined based on performing emergency-department-specific examinations, medication prescriptions, hospital admissions, or transfers. The statistical analysis was performed in SPSS software (version 26). Results: This study included 1080 children with a median age of two years, and the majority of referrals were related to children under the age of three. Furthermore, most good referrals were observed in adolescents (p = 0.001) and most patients were referred between 8 pm and midnight. Cough and nausea or vomiting algorithms were frequently associated with good referrals (p < 0.0001), while rash was commonly associated with poor referrals (p < 0.0001). Only 37.8% of the patients underwent examinations in the emergency department (43.3% were primary-care accessible), 28.3% of the cases required medication in the emergency department, 4.2% of the patients were admitted to hospital care, and 0.4% of the subjects were transferred to another hospital. Viral infectious diseases were the most common discharge diagnosis (52.1%). In addition, over half of the patients did not meet the criteria for a good referral. Discussion: Although phone triage has been believed to be difficult, an excessive number of poor referrals was observed in this study. Accordingly, algorithms should be modified to decrease the chance of unnecessary hospital visits.